PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP AGRESIVITAS PAJAK (Studi empiris pada perusahaan non keuangan yang terdaftar di BEI tahun 2013-2017) - Amalia Madarina; Moh Didik Ardiyanto (Diponegoro Journal of Accounting, 2019)
This study examines how the dimensions of Corporate Social Responsibility (CSR) influence the tax aggressiveness of the company. CSR economic dimension, CSR environmental dimension, and CSR social dimension as independent variables measured by the Global Reporting Initiative (GRI) G4 indexes. Meanwhile, tax aggressiveness is measured by 2 proxies, ETR1 and ETR2.The selection of this research sample was conducted using a purposive sampling method for all Indonesian non-financial companies listed on the Indonesia Stock Exchange in 2013-2017. The number of final samples obtained was 63 consisting of 19 companies over a period of 5 years. Testing this sample uses a multiple regression analysis model.Overall, the study found that CSR economic dimensions have a positive and significant influence on tax aggressiveness as measured by both proxies. CSR environmental dimensions do not have a significant effect on tax aggressiveness using either ETR1 or ETR2. While CSR social dimension has a negative and significant influence on tax aggressiveness with ETR1 proxy and has a positive and significant effect on tax aggressiveness as measured by ETR2 proxy.